2021
DOI: 10.1007/s10570-021-03942-3
|View full text |Cite
|
Sign up to set email alerts
|

Modification of cotton fabrics with 2-diethylaminoethyl chloride for salt-free dyeing with anionic dyes

Abstract: A chemical modification of cotton fabrics by 2-diethylaminoethyl chloride (DEAE-Cl) was achieved, and the resulted cotton fabrics demonstrated salt-free dyeing properties with anionic dyes. Nucleophilic property of hydroxyl groups in cotton cellulose was enhanced under alkaline conditions and could react with DEAE-Cl, a chemical possessing both nucleophilic and electrophilic sites. The monolayered DEAE-grafted cotton cellulose could further react with DEAE-Cl to form multiple cationic quaternary ammonium salts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…Dyeing heat, △H°, represents heat change in the dyeing process. It refers to the heat generated during the transfer of 1 mol of acid dye from the dye bath to spandex in a standard state [ 19 , 20 , 21 , 22 ]. If it is greater than zero, the dyeing process is endothermic; otherwise, it is exothermic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyeing heat, △H°, represents heat change in the dyeing process. It refers to the heat generated during the transfer of 1 mol of acid dye from the dye bath to spandex in a standard state [ 19 , 20 , 21 , 22 ]. If it is greater than zero, the dyeing process is endothermic; otherwise, it is exothermic.…”
Section: Resultsmentioning
confidence: 99%
“…Measuring the dyeing rate curve: the spandex was dyed at 100 °C for 5 min, 10 min, 15 min, 20 min, 30 min, 40 min, 50 min, 60 min, 80 min, 100 min, 120 min, 140 min, respectively, in a dye bath of liquor ratio of 100:1 using 1 g/L acid leveling agent and maintaining a pH of 4.5 (acetic acid-sodium acetate: 10–8 g) [ 19 , 20 , 21 , 22 , 23 ]. The dye concentration was 2% (o.w.f).…”
Section: Methodsmentioning
confidence: 99%
“…R L is the separation factor for assessing whether an adsorption process is favorable (0 < R L < 1) or unfavorable ( R L < 1). 35…”
Section: Methodsmentioning
confidence: 99%
“…To solve this problem, the main strategy has been to change the polysiloxane molecule frame, type and content of hydrophilic substituents, and length of the active siloxane chain segment, but limited success has been obtained. ,, The results showed that adding hydrophilic groups provides better hydrophilicity but leads to worse softness. , Thus, we see that hydrophilicity and softness are difficult to coordinate by changing the functional groups. From the biomimetic strategy, , looking at examples of superhydrophilic structures in nature offers an alternative way to solve the functional synergy of wettability, breathability, and softness.…”
Section: Introductionmentioning
confidence: 99%